Peranan Harem dalam Institusi Sosial dan Politik Uthmaniyyah: The Role of Harem in Ottoman Social and Political Institution - Rosman, Nurul Syafina; Rozali, Ermy Azziaty; Jamsari, Ezad Azraai; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2021)
The history of harem institution has been a subject of interest among researchers on the Ottoman era for the reason of extraordinary involvement of women in administrative affairs of Ottoman politics, military and international relations. The emergence of some prominent Ottoman female figures such as Hurrem Sultan, Kosem Sultan and Turhan Sultan proved that the harem institution is very significant and dynamic.Therefore, the purpose of this article is to study the history of the Ottoman harem institution in general, besides analysing related issues on its role in the social and political aspects. This research uses a qualitative approach through the methods of historical study and content analysis, in gathering and analysing information from relevant materials and academic sources. From the results of the study, this research argues that the main role of the harem institution in the social aspect is the segregation of women to assigned spaces. In the political aspect, the harem has a significant effect on Ottoman administrative affairs, particularly in the 16th and 17th centuries. The harem institution was responsible for the continuity of administration, by giving birth to heirs for the throne and shaping a new dimension for the Ottoman’s international relations or external affairs through the role of diplomatic agents.